2023
DOI: 10.1002/bmm2.12005
|View full text |Cite|
|
Sign up to set email alerts
|

Photo‐facilitated chemodynamic therapeutic agents: Synthesis, mechanisms, and biomedical applications

Abstract: Chemodynamic therapy (CDT) utilizes Fenton and/or Fenton-like reactions in the tumor microenvironment (TME) to produce cytotoxic reactive oxygen species (ROS, mainly hydroxyl radicals, •OH) for inducing cancer cell death. Since CDT exhibits minimal invasiveness and high tumor specificity by responding to TME (overexpressed hydrogen peroxide (H 2 O 2 ) and glutathione (GSH) generation), a lot of related research has been conducted recently. Photo-facilitated CDT can further enhance the catalytic activity and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…Lysosomes contain a large number of hydrolytic enzymes, and targeting the lysosomes can cause rupture, releasing hydrolytic enzymes to digest the entire cell . It is reported that the lysosome-mediated cell death pathway bypassed the classical caspase-dependent apoptotic pathway, which is promising in cancer treatment with antiapoptotic and drug-resistant tumors. , Hence, mBPP NPs are superior nanoplatforms for tumor therapy with satisfactory immunocompatibility, a high uptake rate, and exceptional targeting. Motivated by the excellent 1 O 2 generation of BPA, internal ROS changes from mBPP NPs also were investigated at a more microscopic level.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomes contain a large number of hydrolytic enzymes, and targeting the lysosomes can cause rupture, releasing hydrolytic enzymes to digest the entire cell . It is reported that the lysosome-mediated cell death pathway bypassed the classical caspase-dependent apoptotic pathway, which is promising in cancer treatment with antiapoptotic and drug-resistant tumors. , Hence, mBPP NPs are superior nanoplatforms for tumor therapy with satisfactory immunocompatibility, a high uptake rate, and exceptional targeting. Motivated by the excellent 1 O 2 generation of BPA, internal ROS changes from mBPP NPs also were investigated at a more microscopic level.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 However, the differences between marine and terrestrial environments make it difficult for most conventional wearable sensors to realize underwater sensing applications. 5 Ionogels, with adjustable mechanical characteristics, excellent stretchability, and biocompatibility, are widely explored in ionic skins, 6 soft robots, 7 implantable biomedical devices, 8 and flexible wearable systems. 9 Physical damage and fatigue are inevitable for wearable sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ocean exploration has aroused more and more interest because of the huge resources and special military strategic position. , Wearable underwater sensors are crucially significant in assuring safety and increasing the effectiveness of ocean exploration. , However, the differences between marine and terrestrial environments make it difficult for most conventional wearable sensors to realize underwater sensing applications . Ionogels, with adjustable mechanical characteristics, excellent stretchability, and biocompatibility, are widely explored in ionic skins, soft robots, implantable biomedical devices, and flexible wearable systems .…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) has gained significant attention, primarily for cancer treatment. [14][15][16][17][18][19][20][21][22] However, in the 1990s, researchers discovered the potential of PDT as a powerful tool for combating bacterial infections. Antimicrobial photodynamic therapy (aPDT) employs photosensitizers that produce highly toxic reactive oxygen species (ROS) upon irradiation with an appropriate excitation light source, causing oxidative damage to surrounding lipids, proteins and nucleic acids and ultimately killing pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%